Relationship Between Parenting Self Efficacy And Parenting Stress In Parents Of Children With Special Needs - Rizka Nurlatifah; Fikrie Fikrie (Healthy-Mu Journal, 2022)
This study aims to determine the relationship between parenting self-efficacy and parenting stress on parents of children with special needs. The hypothesis proposed in this study is that there is a relationship between parenting self-efficacy and parenting stress in parents of children with special needs. The subjects of this study are parents who have children with special needs with an age range of 30-55 years. The scale used for data collection is the parenting stress scale with an item power range of 0.400-0.585 and has a Cronbach's alpha reliability value of 0.889 and a parenting self-efficacy scale with an item power range of 0.550-0.883 and has a Cronbach's alpha reliability value of 0.965. The research method used is quantitative with a correlational design and the data analysis used in this study uses Spearman Rho correlation analysis using SPSS 23.0 (Statistical Product and Service Solution). The results of statistical calculations showed a correlation value (r = -.480 ; p < 0.05). These results indicate that there is a relationship between parenting self-efficacy and parenting stress in parents of children with special needs